Reconstruction of Communicative Rationality: A Study on the Digital Mass Media Society in Indonesia - Ribut Priadi; Muhammad Thariq (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2023)
This study examined the cognitive response of Indonesian society (namely, the people who use digital mass media) to the narratives built by digital mass media. Establishing an argumentative “communication” relationship between digital mass media and society is necessary because the narratives built by digital mass media tend to represent particular interests. Therefore, between the two, an argumentative “communication” relationship is needed to reach a consensus through the expression of rational language. This relationship actually forms a communicative society based on the value of emancipatory critical rationality to achieve